Information technology usage in Metro Manila public and private schools - Rodrigo, Ma. Mercedes T (Archīum Ateneo, 2003)
Both public and private schools in the Philippines are using information technology (IT) as a tool to improve teaching and learning. While both government and private sector initiatives indicate national commitment to IT in education, there is little up-to-date information on how extensively the Philippines are using computers and for what purposes. The researcher s goals were to determine the extent to which Metro Manila public and private schools used IT and to determine how these results compared with analogous data on schools in other developing and developed countries. The researcher gathered data with mail-in questionnaires adapted from the International Association for the Evaluation of Educational Achievement (IEA), onsite visits, and follow-up telephone interviews. The researcher also compared her results with those from IEA-surveyed countries. The researcher determined that actual uses of IT did not meet schools curricular goals. Although school officials wanted IT to individualize instruction, promote active learning, and improve student achievement, in actual practice, schools used computers to teach computer literacy, productivity tools, and programming. In terms of infrastructure, the researcher found that schools in Metro Manila had the poorest student-to-computer ratio in comparison to schools in IEA-surveyed countries. Metro Manila students access to peripherals was also poor. Software selections were limited to productivity tools. Students in Metro Manila primary schools, like their counterparts in IEA-surveyed countries, had limited Internet access. A comparison of results from public and private schools revealed that public and private schools shared many educational goals regarding the use of IT. However the realization of these goals was uneven. Private schools had been using computers for a greater number of years than public schools. Private schools had lower student-to-computer and student-to-printer ratios. They also had greater Internet access. Furthermore, private schools tended to expose their students to computers at practically all educational levels. The study provided baseline date that was not previously available. The researcher identifies the need for similar studies with greater geographic scope or of a longitudinal nature, deeper investigations of curricular gaps or policy issues, and the development of instructional software for Filipino-specific subject areas.